2022
DOI: 10.1590/0034-737x202269040003
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological adjustments to shade of jaboticaba tree saplings

Abstract: We aimed to verify the morphophysiological changes in jaboticaba tree (Plinia peruviana (Poir.) Govaerts) saplings under shade gradient to improve knowledge on the appropriate light environmental conditions for the saplings production and field homogeneous or intercropping cultivation of this species. The saplings were grown under full sun and artificial shade levels (30%, 50%, and 80%). Growth, photosynthetic pigments, gas exchanges, chlorophyll fluorescence, and leaf anatomy characters were evaluated. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our results demonstrated that leaf anatomy changes aided in the guabiroba seedlings acclimation to total sunlight condition. In this treatment, the mesophyll (palisade and spongy parenchyma) thickness was responsible for the guabiroba leaf thickness; a similar effect has been observed in other Myrtaceae species (Da Costa et al, 2020;Moura et al, 2022). Inside sun leaves, palisade parenchyma contributes to the propagation efficiency and homogeneity of light, whilst spongy parenchyma promotes increases in the CO 2 diffusion (Barbosa-Campos et al, 2018;Karabourniotis et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…Our results demonstrated that leaf anatomy changes aided in the guabiroba seedlings acclimation to total sunlight condition. In this treatment, the mesophyll (palisade and spongy parenchyma) thickness was responsible for the guabiroba leaf thickness; a similar effect has been observed in other Myrtaceae species (Da Costa et al, 2020;Moura et al, 2022). Inside sun leaves, palisade parenchyma contributes to the propagation efficiency and homogeneity of light, whilst spongy parenchyma promotes increases in the CO 2 diffusion (Barbosa-Campos et al, 2018;Karabourniotis et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…The largest specific leaf area and specific leaf mass were observed in shaded seedlings (Table 3), demonstrating that A. edulis seedlings converted a greater amount of photoassimilates per unit of photosynthetic area, verifying the hypothesis that cultivation under full sun conditions causes changes in morphophysiological responses. An increase in these indices indicates the adaptive ability of leaf tissues to optimize light capture (Moura et al, 2022) as a function of reduced incident radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies portrayed that minimum radiance induces higher chlorophyll pigment content per mass unit [11], being part of the shade stress response. Various tree species displayed different chlorophyll levels under shade conditions [7,10,31]. Otherwise, although carotenoids are crucial in photoprotection under high-light regimes, some plants do not change these contents under light stress [31].…”
Section: Biochemical Traitsmentioning
confidence: 99%
“…Evidence suggests that E. uniflora seedlings exposed to various sunlight conditions can adjust their morphological and physiological characteristics to attain solar irradiation more efficiently [7][8][9][10]. These modifications are called acclimation or phenotypic plasticity, as a genotype's ability to produce diverse phenotypes under different environmental stresses [11].…”
Section: Introductionmentioning
confidence: 99%